(untitled) (Damu Journal of Sport Sciences, 2025)
research aims: 1-Preparing educational exercises using small circles aimed at learning. Some grabs stand for the free wrestlers. 2- Learn the effect of educational exercises by using small circuits in some grabs to stand up for Al Hurra wrestlers. The research hypothesis: - 1 - Educational exercises using small circles have a positive effect on some grabs. The experimental method was used and the research sample was chosen from Al-Adhamiya Sports Club wrestlers aged (10-12) years. The results produced by the tests demonstrated the validity of the educational curriculum used in the research, and its effectiveness in influencing learning the muscat under study. It was recommended to include exercises according to the small-sized circles in the wrestling game as a training or educational method within the vocabulary of the training or educational unit.